Development of an Assessment Instrument for Understanding Physics Concepts and Nationalism Attitudes of Learners on Newton's Laws Material - Ernasari; Nila Mutia Dewi; Ike Lusi Meilina; Rangga Alif Faresta (Postgraduate, University of Mataram, 2025)
This study aimed to develop and validate an assessment instrument to measure students’ understanding of Newton’s laws and their nationalism attitudes. The instrument consisted of 15 essay questions on Newton’s laws and a 30-item Likert-scale questionnaire on nationalism attitudes. Content validity was evaluated by eight experts (lecturers, teachers, and peers) using Aiken’s V index, showing high validity. Empirical validation was conducted with 275 students from public senior high schools in Bima Regency, West Nusa Tenggara. Data were analyzed using Item Response Theory with the Partial Credit Model (PCM) via QUEST. Results indicated that all concept understanding items fit the PCM criteria, with acceptable reliability values ranging from 0.72 to 0.98. For the nationalism instrument, 29 items met the fit criteria, while one item was rejected. Overall, the developed instruments demonstrated strong validity and reliability, and are suitable for assessing both cognitive understanding of Newton’s laws and students’ nationalism attitudes.